Biocatalytic Degradation Efficiency of Postconsumer Polyethylene Terephthalate Packaging Determined by Their Polymer Microstructures. Issue 14 (20th May 2019) - Wei, Ren; Breite, Daniel; Song, Chen; Gräsing, Daniel; Ploss, Tina; Hille, Patrick; Schwerdtfeger, Ruth; Matysik, Jörg; Schulze, Agnes; Zimmermann, Wolfgang
Abstract: Polyethylene terephthalate (PET) is the most important mass‐produced thermoplastic polyester used as a packaging material. Recently, thermophilic polyester hydrolases such as TfCut2 from Thermobifida fusca have emerged as promising biocatalysts for an eco‐friendly PET recycling process. In this study, postconsumer PET food packaging containers are treated with TfCut2 and show weight losses of more than 50% after 96 h of incubation at 70 °C. Differential scanning calorimetry analysis indicates that the high linear degradation rates observed in the first 72 h of incubation is due to the high hydrolysis susceptibility of the mobile amorphous fraction (MAF) of PET. The physical aging process of PET occurring at 70 °C is shown to gradually convert MAF to polymer microstructures with limited accessibility to enzymatic hydrolysis. Analysis of the chain‐length distribution of degraded PET by nuclear magnetic resonance spectroscopy reveals that MAF is rapidly hydrolyzed via a combinatorial exo‐ and endo‐type degradation mechanism whereas the remaining PET microstructures are slowly degraded only by endo‐type chain scission causing no detectable weight loss. Hence, efficient thermostable biocatalysts are required to overcome the competitive physical aging process for the complete degradation of postconsumer PET materials close to the glass transition temperature of PET. Abstract : Postconsumer polyethylene terephthalate (PET) packaging materials are efficiently degraded by the polyester hydrolase TfCut2 resulting in a weight loss of 50% after 96 h at 70 °C. The mobile amorphous fraction of PET is degraded preferentially by the enzyme. NMR analysis suggests a combined exo‐ and endo‐type hydrolysis of the polymer chains.